PENANGANAN PNEUMONIA PADA ANAK DENGAN CLAPPING - Ema Trisnawati; Difto Restu Putra Haryono; Condrovisoko Rochman Utomoputro; Dini Nur Alpiah (Jurnal Kesehatan, 2025)
The quality of the environment in which children live significantly impacts their respiratory health. In densely populated areas, children often face challenges such as poor air circulation at home and constant exposure to cigarette smoke from the environment or family members. This unhealthy environment plays a significant role as a major risk factor for high cases of respiratory diseases, including pneumonia, in children. This study aims to describe the procedure for implementing clapping in children with pneumonia, analyze the challenges faced in its implementation, and evaluate the effectiveness and patient response to this intervention. The research method used a literature review and case report analysis. The evaluation results show that providing clapping systematically and integratedly can reduce respiratory frequency, reduce rhonchi sounds, improve oxygen saturation, and increase patient comfort and activity. Therefore, the success of therapy is greatly influenced by the skills of the physiotherapist, close clinical monitoring, education to the family, and parental commitment in supporting the home program.